Walking and Collecting: How can our thinking on materials and process in contemporary collection-based art be realised through the act and purpose of walking? - Smith , Amber (Journal of Public Pedagogies, 2020)
Walking and art have long been intertwined, much like collecting and art. As best put by artist Patrick Pound, it’s the notion of a ‘gathering of thoughts, through things’ (Pound, 2017) – a way of combatting the dispersive and entropic nature of the artefact-centric world we live in. Walking is it the ‘modality of lived experience’ (Forgione, 2005); an everyday, routine activity and yet one that as conscious beings, we know to be much more than just walking. What walking and collecting share is a preoccupation with time, scope, and a need to find a sense of completion to – or perhaps dominion over – the overwhelming expanse of our existence. It can then be theorised that walking and collecting when done in unison, are the process and method that provide the artist with the contextual and conceptual mechanisms for the acquisition and subsequent display of these thoughts.